Plasma dynamic synthesis of composite ZnO-Bi2O3 material with a core-shell structure for varistor ceramics; Ceramics International; Vol. 44, iss. 18 - Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Shanenkova Yu. L. Yuliya Leonidovna; Shanenkov I. I. Ivan Igorevich; Rakhmatullin I. A. Ilyas Aminovich; Osokina L. V. Liliya Vitaljevna (2018, 2018)
Title screen